Students' understanding of the greenhouse effect : a cross-age study - Özçelik, Ceren. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
This study aimed to investigate high school students’ and final- year pre-service teachers’ mental models of the greenhouse effect at different age levels (Grade 9, Grade 11, and the pre- service teachers). This study further investigated the relation between students’ mental models and academic achievements. In this regard, the study identified the components and properties of the mental models of each participant about the greenhouse effect and explored how the main constituents of these models progressed across different grade levels. Secondly, the mental models of the greenhouse effect were examined based on the participants' academic achievement. For this purpose, individual interviews were conducted with high school students: Grade 9 (n=18) aged between 14-16, Grade 11 (n=24) aged between 17-19, and pre-service physics and chemistry teachers (n=19), who were 18-29 years old. This study used qualitative data from semi-structured interviews and sketches to identify the participants' mental models about the greenhouse effect. The constant comparative method was used to analyze student answers to questions about the greenhouse effect. The data was iteratively coded to generate the codes corresponding to students’ mental models about the mechanism of the greenhouse effect. The features of greenhouse effect mechanisms and ten different mental models were identified. The Macro Models without particulate level explanations outnumbered the Micro Models in which the properties of particles are explained across all participant groups. Pre-service teachers have significantly progressed toward a scientific greenhouse effect model compared to the other groups. Alternative conceptions of the students about the greenhouse effect were also identified. Each student’s academic accomplishment based on their grade point average was related to the type of their mental model. No correlation was found between academic achievement and the types of mental models of the Grade 9 students’ mental models. However, there was a moderately significant correlation between the mental models of the Grade 11 students and the pre-service teachers.
Keywords: Cognitive psychology.; Teachers -- Self-rating of.; Greenhouse effect, Atmospheric -- Study and teaching.